Analysis of a car door subjected to side impact - Long, Christopher Robert (Blast Impact and Survivability Research Unit, 2016)
The study presented in this thesis focuses on the response of a side impact beam located in a car door to impact loading in close conformation to the Federal Motor Vehicle Safety Standard 214 (FMVSS 214) standard. The side impact beam is situated in both the front and rear side doors of a vehicle between the inner and outer shells to minimise intrusion into the passenger compartment whilst absorbing as much impact energy as possible in a collision. While some manufacturers use tubular side impact beams, others use corrugated structures. Different materials are also considered, depending on the class of vehicle, a nd market for which it is intended. In this study, a numerical model of a light -weight passenger car, developed by the National Crash Analysis Center (NCAC ) of The George Washington University under contract with the Federal Highway Administration (FHWA) and National Highway Traffic Safety Administration (NHTSA ) of the United States Department of Transportation (US DOT ), was used to simulate a side impact on the front side door using the LS -DYNA R7.1.1 explicit solver . The resulting deformation of the door from the full vehicle model was used to design an experiment for an impact test on a passenger door, which was used to validate an equivalent numerical simulation. In the experiments, the car door was modified and subjected to a drop mass of 385 kg from a height of 1.27 m. The drop mass and height were chosen such that the maximum deflection in the car door impact test would be of similar magnitude to the deflecti n of the door in full vehicle model when subjected to an impact load in accordance with the FMVSS 214 Standard - which requires that the vehicle be projected into a rigid vertical 10 inch diameter pole at 29 km/h in a direction 75° to the longitudinal axis of the vehicle . The results from the numerical simulation of the struck door test were in good agreement with the experiments in both shape and magnitude of deformation. The behaviour of the side impact beam located in the passenger door was isolated and further studied. Drop test experiments on beams with square and round cross -sections were carried out to validate the equivalent finite element model. The drop mass and height of the striker was varied such that the transient response of the isolated side impact beam matched the response of the beam in the simulation of the equivalent door model and full vehicle model. In the impact test experiments, the tubular structures were subjected to a 200 kg mass dropped from six incrementally varying heights of 250- 500 mm. Both square and round tubes were observed to buckle at approximately 835 mm from the free end with different magnitude s of maximum deformation (depending on the drop height). The results from the numerical simulations showed good correlation with the experiments for shape and magnitude of deformation. A quadratic curve fit to the experimental maximum transverse deflection resulted in an R -squared value of 0.92 and 0.96 for the square and round tubes respectively. A parametric study was carried out on the side impact beam to investigate the effect of: Thickness and material of a singular tube configuration, and: Inner tube length and outer tube thickness of a compound tube structure. The performance of the different configurations were assessed in terms of Crash Force Efficiency (CFE and Specific Energy Absorption (SEA). A parametric study on the effect of the tube thickness showed that thicker tubes of the same material exhibited deformation of lo wer magnitude and had lower SEA. Aluminium tubes absorbed two or more times the energy per unit mass than the equivalent steel tubes. A round aluminium tube with a thickness of 2.175 mm was found to give the best balance between SEA and maximum deflection with values of 1.5 kJ/kg and 350 mm respectively. The compound tube configuration with the inner tube extended beyond the buckling point performed better in terms of SEA and maximum deflection provided the length of the inner tube did not exceed 90% of the length of the outer tube. The optimised compound tube configuration performed better than the single tube configuration in the full vehicle model with a 1mm reduction in the overall intrusion of the rigid pole.